ANALISIS OPERASI PINTU SADAP Studi Kasus DI Kuton dan DI Dadapan - , ERNI MULYANDARI; , Prof. Dr. Ir. Fatchan Nurrochmad, M.Agr ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Weir in irrigation areas are always equipped with intake gate. The intake gate has several function for examples to tapping the flow from river, setting entry of water into irrigation canals. In recent years, often occurs operation of intake gate that doesn't fit such as when summer comes, water supply sometimes unable to complete the water requirements of farmers and when rainy season comes, the available water canât be used optimally. The aim of this research is to analyze the intake gate operation. The intake gate operation was analyzed using quantification method 1. The items used in this analysis were made into 2 alternatives. The first alternative consists of the discharge gate operation yesterday, the discharge gate operation two days ago and three days ago, the rain today, the rain yesterday, the amount of rain two days ago and the amount of rain three days ago. The second alternative consists of the discharge gate operation yesterday, the discharge gate operation two days ago and three days ago, the rain today, the rain yesterday, the amount of rain two days ago and the amount of rain three days ago, and the periods of crop growth. The results of this research show that intake gate operation in Kuton irrigation area is classified very good and in Dadapan irrigation area is classified good. Itâs seen from the value of multiple correlation coefficient between the actual discharge with the prediction discharge of intake gate operation amount 0,82 and in irrigation area Dadapan amount 0,70. The item of crop growth periods in irrigation areas of Kuton and Dadapan get less attention from the operators so it doesn't improve the performance of the intake gate operation.